Structure and magnetism of a tetrahedral uranium(iii) β-diketiminate complex. Issue 23 (4th June 2020) - Boreen, Michael A.; Gould, Colin A.; Booth, Corwin H.; Hohloch, Stephan; Arnold, John
Abstract : A rare tetrahedrally coordinated uranium(iii ) complex supported by β-diketiminate ligands is synthesized and investigated for its magnetic properties. Abstract : We describe the functionalisation of the previously reported uranium(iii ) β-diketiminate complex (BDI)UI2 (THF)2 (1 ) with one and two equivalents of a sterically demanding 2, 6-di iso propylphenolate ligand (ODipp) leading to the formation of two heteroleptic complexes: [(BDI)UI(ODipp)]2 (2 ) and (BDI)U(ODipp)2 (3 ). The latter is a rare example of a tetrahedral uranium(iii ) complex, and it shows single-molecule magnet behaviour.